# Can someone please help me? I have this part figured out.$15660x2/3x1/2=5220.($15660-5220)x2/3=6960. ($15660-answer)x2/3=answer.($15660-answer)-$600=answer.Now I need this part figured out.

### 1 Answer | Add Yours

It appears that you are confused because the way various expressions are represented, these can be interpreted in different ways. You can represent the expression more clearly as:

Instead of:

### I.

### 15660x2/3x1/2=5220.

15660 x (2/3) x (1/2) = 5220

This can be simplified as:

==> 15660 x (2x1)/(3x2) = 5220

==> 15660 x (1/3) = 5220

==> 15660/3) = 5220

In this case:

($15660 - answer) x (2/3) = answer, becomes

($15660 - 5220) x (2/3) = 5220

### II.

Similarly Instead of:

### (15660-5220)x2/3=6960.

(15660 - 5220) x (2/3) = 6960

This can be simplified as:

==> (10440) x (2/3) = 6960

==> (10440 x 2)/3 = 6960

==> 20880/3 = 6960

In this case:

($15660 - answer) - $600 = answer, becomes,

($15660 - 6960) - $600 = 6960

Please note that this equation is not correct. There appears to be some error in question posted. The correct value of ($15660 - 6960) - $600 is 8100

This equation can be balanced with value of answer as 7530. Then the equation becomes:

($15660 - 7530) - $600 = 7530